2021
DOI: 10.1111/pde.14878
|View full text |Cite
|
Sign up to set email alerts
|

A fatal case of malignant atrophic papulosis in a pediatric patient

Abstract: A 17‐year‐old Caucasian boy presented with progressive left‐sided weakness, transient slurred speech, and skin lesions characterized by 3‐5 mm, pink, asymptomatic papules with white atrophic centers on his central abdomen, back, and lower extremities. Skin biopsy confirmed the diagnosis of malignant atrophic papulosis, a rare vasculopathy that leads to the occlusion of small‐ and medium‐sized arteries. He was treated with cyclophosphamide, eculizumab, treprostinil, pentoxifylline, heparin, and acetylsalicylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Treprostinil was not used in the patient due to high costs and insurance challenges. However, although eculizumab and treprostinil have been continued, progressive neurologic, pleural, and pericardial MAP has been reported ( 4 , 35 ). A recent study has revealed that the obliterative proliferative neointimal arteriopathy and the sclerodermic fibrosing serositis occur independently of complement inhibition, and both of them occurred in patients exhibiting complete blockade of complement on eculizumab ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treprostinil was not used in the patient due to high costs and insurance challenges. However, although eculizumab and treprostinil have been continued, progressive neurologic, pleural, and pericardial MAP has been reported ( 4 , 35 ). A recent study has revealed that the obliterative proliferative neointimal arteriopathy and the sclerodermic fibrosing serositis occur independently of complement inhibition, and both of them occurred in patients exhibiting complete blockade of complement on eculizumab ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The available data on pAP mainly derives from case reports and, interestingly, from articles mostly published in neurological journals (Table 1). 3,6,9–41 Atrophic papulosis is considered to affect middle‐aged adults. However, a substantial number of patients in our cross–sectional study were children (20%; 19/96).…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of case reports of paediatric atrophic papulosis (pAP) is constantly growing (Table 1). 3,6,9–41 Our study aimed to investigate the early occurrence of the disease, including congenital manifestations, and to compare this to adult atrophic papulosis (aAP).…”
Section: Introductionmentioning
confidence: 99%
“…A case of cutaneous necrotizing eosinophilic vasculitis was successfully treated with prednisolone, pentoxifylline, and nifedipine 15 . Three cases describe the use of pentoxifylline in conjunction with other therapies for malignant atrophic papulosis 16–18 …”
Section: Vascularmentioning
confidence: 99%
“…15 Three cases describe the use of pentoxifylline in conjunction with other therapies for malignant atrophic papulosis. [16][17][18]…”
Section: Vasculitis and Vasculopathiesmentioning
confidence: 99%